Concepções e práticas declaradas de ensino e aprendizagem com TDIC em cursos de Licenciatura em Matemática - Lopes, Rosemara Perpetua [UNESP] (2014)
The present research enrolled in the line “Formative Practices and Processes in Education” was originated in the Master program research through document analysis that indicated two Mathematics major courses from a Sao Paulo State university, as those that foresaw the training for the use of Digital Information and Communication Technology (DICT) in their pedagogical projects. Starting from these results, one aims to clarify how this training occurs. One supports the hypothesis that features separate settings at the documental level and at the level of practice declared by the individuals. Therefore, one has as main objective investigate the training referred at the concrete level of the courses, according to the declared concepts and practice of the protagonists. The specific objectives are: analyze how the joint occurs between mandatory and optional subjects, pointed in the projects as a means to promote such training; identify the conceptions of student teachers about teaching and learning with DICT; highlight the conceptions of trainer teachers and course coordinators about teaching with DICT; investigate situations that, from the point of view of the individuals, have provided training in the use of technology. To achieve these goals, one develops a qualitative study with a questionnaire to students in the last year course in 2011, and semi-structured interviews of the teachers who taught subjects involved in training these students, and course coordinators of the referred courses. Concerning the objectives, the research question and hypothesis, it appears that the planned joint in the educational projects does not occur in these courses. The conceptions are analyzed regarding the pedagogical approach as instructionist or constructionist, and the opening, understood as “predisposition to”, as optimist, pessimist or realistic...